Pengaruh Heriditas Terhadap Perilaku Anak Usia Dini Di Lembaga Pendidikan Islam - Musleh Musleh; Sri Agustin; Tolak Ida (Dirosat : Journal of Islamic Studies, 2020)
This research article is about the influence of heredity on early childhood behavior in Islamic educational institutions. The focus of this research is to determine the effect of heredity on the behavior of students. To know the influence of heredity and environment. To know the influence of heredity and environment on individual development. In this study the authors used a qualitative research approach with a descriptive method. The results of this study are that heredity and environment have a close relationship. The two complement each other, nothing can separate them. The impact on individuals is also enormous. Especially heredity where most individuals have disabilities when they are born. The environment will only influence individuals when they are ready to accept it. If not, then the result will be the same as heredity, there will be defects in his personal nature.